The Influence of Financial Experience, Education Level and Accounting Understanding on the Preparation of Financial Reports of Msmes Based on EMKM SAK for UMKM Actors in Medan City - Nagita Wulandari; Nur Aliah (Jurnal Multidisiplin Sahombu, 2025)
This study aims to examine the influence of financial experience, educational level, and accounting comprehension on the preparation of financial statements of Micro, Small, and Medium Enterprises (MSMEs) based on SAK EMKM (Financial Accounting Standards for MSMEs) in the city of Medan. The research employed a quantitative approach with 100 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that financial experience and accounting comprehension have a positive and significant influence on the preparation of financial statements. Educational level also has a significant influence, though to a lesser extent. Simultaneously, all three variables significantly affect the quality and compliance of MSME financial reporting with SAK EMKM standards. These findings suggest that enhancing MSME actors’ financial experience and accounting knowledge, supported by an adequate educational background, can improve their ability to produce standardized, accurate, and reliable financial reports.